2013
DOI: 10.1098/rsbl.2013.0633
|View full text |Cite
|
Sign up to set email alerts
|

It is all in the face: carotenoid skin coloration loses attractiveness outside the face

Abstract: Recently, the importance of skin colour for facial attractiveness has been recognized. In particular, dietary carotenoid-induced skin colour has been proposed as a signal of health and therefore attractiveness. While perceptual results are highly consistent, it is currently not clear whether carotenoid skin colour is preferred because it poses a cue to current health condition in humans or whether it is simply seen as a more aesthetically pleasing colour, independently of skin-specific signalling properties. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 25 publications
4
47
0
Order By: Relevance
“…Given the assumption that levels of sex hormones remain relatively stable between puberty and menopause, current sex hormone levels can be seen as a proxy for pubertal hormone levels, mirroring the hormonal state of the critical pubertal period. Similar assumptions have been made in research looking at associations between hormone levels and facial appearance in men (e.g., Lefevre, Ewbank, Calder, von dem Hagen, & Perrett, 2013;Penton-Voak & Chen, 2004;Pound, Penton-Voak, & Surridge, 2009 A c c e p t e d M a n u s c r i p t 16 We note that in the present study we focused only on shape information. Several studies suggest that other information, such as for example facial surface information (skin colour or texture) also influences perceptions of attractiveness (Fink et al, 2001;Lefevre et al, 2013).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Given the assumption that levels of sex hormones remain relatively stable between puberty and menopause, current sex hormone levels can be seen as a proxy for pubertal hormone levels, mirroring the hormonal state of the critical pubertal period. Similar assumptions have been made in research looking at associations between hormone levels and facial appearance in men (e.g., Lefevre, Ewbank, Calder, von dem Hagen, & Perrett, 2013;Penton-Voak & Chen, 2004;Pound, Penton-Voak, & Surridge, 2009 A c c e p t e d M a n u s c r i p t 16 We note that in the present study we focused only on shape information. Several studies suggest that other information, such as for example facial surface information (skin colour or texture) also influences perceptions of attractiveness (Fink et al, 2001;Lefevre et al, 2013).…”
Section: Discussionmentioning
confidence: 71%
“…Similar assumptions have been made in research looking at associations between hormone levels and facial appearance in men (e.g., Lefevre, Ewbank, Calder, von dem Hagen, & Perrett, 2013;Penton-Voak & Chen, 2004;Pound, Penton-Voak, & Surridge, 2009 A c c e p t e d M a n u s c r i p t 16 We note that in the present study we focused only on shape information. Several studies suggest that other information, such as for example facial surface information (skin colour or texture) also influences perceptions of attractiveness (Fink et al, 2001;Lefevre et al, 2013). It seems that, particularly in women, both shape and surface information are relevant for an attractive appearance (Torrance, Wincenciak, Hahn, DeBruine, & Jones, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…Hagen, & Perrett, 2013;Re, Whitehead, Xiao, & Perrett, 2011;Tan & Stephen, 2013). This suggests that skin color plays an important role in social communication.…”
Section: Emotion-color Associationsmentioning
confidence: 99%
“…The task was completed individually online through the university intranet (virtual classroom). Previous research on face perception has demonstrated that laboratory and online studies produce equivalent results (e.g., DeBruine, Jones, Unger, Little, & Feinberg, 2007;Lefevre, Ewbank, Calder, von dem Hagen, & Perrett, 2013).…”
Section: Methodsmentioning
confidence: 99%